Negative Association Between Mediterranean Diet Adherence and COVID-19 Cases and Related Deaths in Spain and 23 OECD Countries: An Ecological Study - Greene, Michael W.; Roberts, Alexis P.; Frugé, Andrew D. (Frontiers in Nutrition, 2021)
In December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-Cov2) emerged in Wuhan, China, sparking the Coronavirus disease 2019 (COVID-19) pandemic. The high prevalence of nutrition-related COVID-19 risk factors including obesity, type 2 diabetes, and hypertension, suggests that healthy dietary approaches may mitigate COVID-19 related outcomes and possibly SARS-CoV-2 infection. Based on the fundamental role of nutrition in immune function and the well documented association between Mediterranean diet consumption and risk reduction for chronic diseases that are comorbidities in COVID-19 patients, we hypothesized that there would be a relationship between Mediterranean diet adherence and COVID-19 cases and related deaths. In this perspective, we examined the association between regional adherence to a Mediterranean diet and COVID-19 cases and deaths using an ecological study design. We observed that Mediterranean diet adherence was negatively associated with both COVID-19 cases and related deaths across 17 regions in Spain and that the relationship remained when adjusted for factors of well-being. We also observed a negative association between Mediterranean diet adherence and COVID-19 related deaths across 23 countries when adjusted for factors of well-being and physical inactivity. The anti-inflammatory properties of the Mediterranean diet - likely due to the polyphenol content of the diet - may be a biological basis to explain our findings. However, there are confounding factors unrelated to dietary factors driving COVID-19 cases and related deaths across the regions in Spain and the 23 countries examined in our analysis. Our findings will need to be confirmed and further explored in cohort studies.